Knowledge, Attitudes and Practice of Pregnant Women about Anemia during Pregnancy in Baghdad Teaching Hospital - Saeed, Ruaa Safaa (South Asian Journal of Social Sciences and Humanities, 2024)
Objectives: to assess the level of knowledge, attitude and practice of pregnant women about anemia. To assess the association between knowledge of pregnant women and their socio – demographic variances. To assess the association between the practice of pregnant women and their socio – demographic variances. Methods: cross sectional study, carried out among pregnant at Baghdad Teaching Hospital, from 25th February to 28th April, 2023. A total of 300 pregnant women participated in the study. The tool of study was questionnaire. Results: The study revealed 63.3% of pregnant women had good knowledge, positive attitude found in 65.3% and health practice in 59.3% among pregnant women regarding anemia, the study show association between the knowledge of the pregnant woman and educational level of her and her husband, also there is association between the practice of pregnant woman and her occupation. Conclusion: A noticeable general good level of knowledge , attitude and practice among pregnant women regarding anemia during pregnancy, level of knowledge in pregnant woman associated with the educational level of her and her husband and healthy practice increase in employed pregnant woman. Recommendations: Raise the level of knowledge and practice for prevention, learn pregnant women healthy dietary habit and encourage pregnant women to early registration in primary health care center.